Office-Based Three-Dimensional Printing Workflow for Craniomaxillofacial Fracture Repair. Issue 5 (July 2018) - Elegbede, Adekunle; Diaconu, Silviu C.; McNichols, Colton H.L.; Seu, Michelle; Rasko, Yvonne M.; Grant, Michael P.; Nam, Arthur J.
Abstract : Abstract: Three-dimensional printing of patient-specific models is being used in various aspects of craniomaxillofacial reconstruction. Printing is typically outsourced to off-site vendors, with the main disadvantages being increased costs and time for production. Office-based 3-dimensional printing has been proposed as a means to reduce costs and delays, but remains largely underused because of the perception among surgeons that it is futuristic, highly technical, and prohibitively expensive. The goal of this report is to demonstrate the feasibility and ease of incorporating in-office 3-dimensional printing into the standard workflow for facial fracture repair. Patients with complex mandible fractures requiring open repair were identified. Open-source software was used to create virtual 3-dimensional skeletal models of the, initial injury pattern, and then the ideally reduced fractures based on preoperative computed tomography (CT) scan images. The virtual 3-dimensional skeletal models were then printed in our office using a commercially available 3-dimensional printer and bioplastic filament. The 3-dimensional skeletal models were used as templates to bend and shape titanium plates that were subsequently used for intraoperative fixation. Average print time was 6 hours. Excluding the 1-time cost of the 3-dimensional printer of 2500, roughly the cost of a single commercially produced model, the average material cost to print 1 model mandible was 4.30. Postoperative CT imaging demonstrated precise, predicted reduction in all patients. Office-based 3-dimensional printing of skeletal models can be routinely used in repair of facial fractures in an efficient and cost-effective manner.